Individual and Regional-level Factors Contributing to Variation in Length of Stay After Cerebral Infarction in Six European Countries - Peltola, Mikko; Seppälä, Timo T; Malmivaara, Antti; Belicza, Éva; Numerato, Dino; Goude, Fanny; Fletcher, Eilidh; Heijink, Richard; EuroHOPE study group (Health economics, 2015)
Using patient-level data for cerebral infarction cases in 2007, gathered from Finland, Hungary, Italy, the Netherlands, Scotland and Sweden, we studied the variation in risk-adjusted length of stay (LoS) of acute hospital care and 1-year mortality, both within and between countries. In addition, we analysed the variance of LoS and associations of selected regional-level factors with LoS and 1-year mortality after cerebral infarction. The data show that LoS distributions are surprisingly different across countries and that there is significant deviation in the risk-adjusted regional-level LoS in all of the countries studied. We used negative binomial regression to model the individual-level LoS, and random intercept models and ordinary least squares regression for the regional-level analysis of risk-adjusted LoS, variance of LoS, 1-year risk-adjusted mortality and crude mortality for a period of 31-365 days. The observed variations between regions and countries in both LoS and mortality were not fully explained by either patient-level or regional-level factors. The results indicate that there may exist potential for efficiency gains in acute hospital care of cerebral infarction and that healthcare managers could learn from best practices.
Keywords: cerebrální infarkt; délka pobytu; cerebral infarction; Aged; Aged, 80 and over; regional variation; lidé středního věku; senioři; length of stay; lidé; Adult; Middle Aged; dospělí; Europe; Female; senioři nad 80 let; Male; ženské pohlaví; Cerebral Infarction; mladý dospělý; Humans; mužské pohlaví; Young Adult; Length of Stay; regresní analýza; Regression Analysis; Evropa